Behavioral and Immunological Features Promoting the Invasive Performance of the Harlequin Ladybird Harmonia axyridis - Verheggen, François J.; Vogel, Heiko; Vilcinskas, Andreas (Frontiers in Ecology and Evolution, 2017)
The harlequin ladybird Harmonia axyridis is now established as a model to test hypotheses explaining why some species become successfully invasive, while others, even closely related ones, do not. In this review, we evaluate behavioral and immunological features that may play a role in the invasive performance of this model species. We discuss the behavioral traits and associated semiochemicals that promote the invasive success of H. axyridis. In particular, we consider (1) the aggregative behavior and the particular role of long-chain hydrocarbons; (2) the importance of sex pheromones and non-volatile chemicals in mate location and selection; (3) the use of allelochemicals for prey location; and (4) the nature of chemicals that protect against natural enemies. We also highlight the superior immune system of H. axyridis, which encompasses a broader spectrum of antimicrobial peptides (and higher inducible expression levels) compared with native ladybird beetles such as Adalia bipunctata and Coccinella septempunctata. The chemical defense compound harmonine and the antimicrobial peptides are thought to confer resistance against the abundant microsporidia carried by H. axyridis. These parasites can infect and kill native ladybird species feeding on H. axyridis eggs or larvae, supporting the hypothesis that intraguild predation plays a role in the ability of H. axyridis to outcompete native ladybird species in newly-colonized areas.